2020
DOI: 10.21037/jtd.2019.07.81
|View full text |Cite
|
Sign up to set email alerts
|

Chest wall resection and reconstruction for lung cancer: surgical techniques and example of integrated multimodality approach

Abstract: wall resection and reconstruction for lung cancer: surgical techniques and example of integrated multimodality approach. J

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 43 publications
1
10
0
1
Order By: Relevance
“…Our surgical treatment of chest wall tumors accords well, in all cases, with an approach on the reconstruction procedure of a post-excision defect in the sternocostal framework reported in [ 1 , 3 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Artificial rib constructs for thoracic osteosynthesis prepared pursuant to a 3D model were a proper fit when the defect was being reconstructed and did not require any intraoperative correction ( Figure 1 ), and thus the surgery time was shortened, as indicated in Table 3 .…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…Our surgical treatment of chest wall tumors accords well, in all cases, with an approach on the reconstruction procedure of a post-excision defect in the sternocostal framework reported in [ 1 , 3 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Artificial rib constructs for thoracic osteosynthesis prepared pursuant to a 3D model were a proper fit when the defect was being reconstructed and did not require any intraoperative correction ( Figure 1 ), and thus the surgery time was shortened, as indicated in Table 3 .…”
Section: Resultssupporting
confidence: 70%
“…Despite the significant progress made in various areas of oncosurgery, the surgical stage in treating chest wall tumors occupies the leading position [ 3 , 4 , 5 , 6 , 7 ]. Radical surgical intervention for chest wall tumors is typically accompanied by the lesion of osteochondral structures and the appearance of complex post-resection defects, which result in functional and aesthetic impairment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the tolerability of surgery following induction chemoradiotherapy may be decreased and the risk of postoperative complications increased because of impaired respiratory function (16). Although the morbidity rate associated with chest wall resection and reconstruction ranges from 24% to 46% and that for mortality ranges from 2% to 7% (11)(12)(13)(14), there was no mortality in our study and Clavien-Dindo grade >IIIa postoperative complications occurred at a rate of 16.7%, which might be tolerable.…”
Section: Discussionmentioning
confidence: 58%
“…In one study, the 5-year survival rate was reported to be 32% in 175 patients with complete resection and 4% in 94 patients with incomplete resection (10). Furthermore, the survival rate ranges from 8.0% to 21.0% for patients with pN2 disease and from 25.0% to 67.0% for those with pN0 disease (11)(12)(13)(14). Therefore, in addition to complete resection, preoperative mediastinal lymph node staging is recommended to exclude N2 disease, and if pathologically proven, the patient should receive multimodal therapy in view of the otherwise poor prognosis.…”
Section: Discussionmentioning
confidence: 99%